(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
The paper presents the important elements for the design of an HTS superconducting electromagnet, generator of an intense magnetic field (5T) and of high uniformity (<1%). To establish its geometric and functional parameters, the value of the induction of the generated magnetic field and the uniformity in its central area were taken into consideration. Numerical modeling of the generated magnetic field was performed in Comsol Multiphysics. The characteristics of the YBCO type HTS superconducting material were also taken into account. The coils will be made in the form of double buckets of superconducting tape, the chosen configuration being Helmholtz type. In this way, the central magnetic field area of ​​the electromagnet is accessible for applications from two directions: vertical and horizontal.